Extinctions of interactions: quantifying a dung beetle-mammal network - Raine, E; Mikich, S; Lewis, O; Riordan, P; Vaz-De-Mello, F; Slade, E (Ecological Society of America, 2018)
Loss of large‐bodied mammals across the globe through hunting, habitat degradation, and fragmentation is one of the most significant anthropogenic impacts on the environment. Cascading effects of these extinctions through ecosystems have been little studied, although correlative studies have revealed co‐extinctions in closely linked groups, with implications for ecosystem structure and function. Despite playing important roles in seed dispersal and hence seedling recruitment, mammals have been largely neglected in network studies. Similarly, the role of secondary seed dispersers, such as ants and dung beetles, has been largely unexplored. Most dung beetles rely on mammal feces for feeding and breeding and provide a suite of important ecosystem functions and services. While dung beetle community responses to environmental change have been widely investigated, studies quantifying the network of associations between dung beetle and mammal species are lacking. By developing the first quantitative mammal–dung beetle networks, we address several important knowledge gaps contributing to the understanding of how interactions in networks involving mammals and secondary insect seed dispersers are structured. We use the resulting quantitative interaction networks to model mammal species extinction scenarios to further explore the consequences for dung beetle populations, and the extent to which networks change the strength of interactions through resource switching. Dung beetle feeding and breeding networks did not differ significantly in structure and showed high nestedness and low levels of trophic specialization. Simulations suggested that mammal extinction scenarios based on mammal body mass and mammal dung volume will impact dung beetle populations to a greater extent than random scenarios of mammal loss. Thus, despite their generalist feeding preferences, realistic mammal extinction scenarios have the potential to negatively impact the dung beetle community, which may have consequences for ecosystem functioning.